Teaching and learning of english as a second language issues, challenges and opportunities - Zainurin Abdul Rahman 1968- (Institut Terjemahan dan Buku Malaysia, 2016)
This book is a collection of research reports and concepts papers on the teaching and learning of English as a Second Language (ESL). The book attempts to highlights certain issues that are considered critical in improving the teaching and learning process of English Language. The topics discussed in this book include the training of pre-service teachers, the teaching of literature component in Malaysian schools, note-taking strategies as useful tools for language learners, the use of authoring software in English Language teaching and the practice of assessment for students' placement purposes. The strength of this book lies in the wide-ranging topics of its content and the easy-to-read manner the book is written. This makes the book a suitable reading material for teachers, language instructors and tertiary students